2018
DOI: 10.1245/s10434-018-6758-1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Cost for Pancreatic Surgery: It’s Not About Hospital Volume

Abstract: While high-volume hospitals have fewer adverse outcomes, there is no relationship between surgical volume and costs, which suggests that, in itself, surgical volume is not an indicator of improved healthcare efficiency reflected by lower costs. Patient referral to high-volume centers may not reduce overall healthcare expenditures for pancreatic operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Enomoto et al (45) added in an analysis of 3137 patients from the NIS database that the costs for patients treated by low-volume surgeons at LVCs are higher than those for patients treated by low-volume surgeons at HVCs. On the contrary, large retrospective series by Gani et al (32) (11,081 PR patients) and Bateni et al (21) (27,653 PR patients) found no significant association between costs and operation volume.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Enomoto et al (45) added in an analysis of 3137 patients from the NIS database that the costs for patients treated by low-volume surgeons at LVCs are higher than those for patients treated by low-volume surgeons at HVCs. On the contrary, large retrospective series by Gani et al (32) (11,081 PR patients) and Bateni et al (21) (27,653 PR patients) found no significant association between costs and operation volume.…”
Section: Resultsmentioning
confidence: 88%
“…They stated that the OR for morbidity was 1.39–1.47 in low or medium volume centers compared with HVCs. Bateni et al (21) (27,653 patients) and Mehta et al (31) (2453 patients) analyzed the postoperative results of PRs and concluded that there were significantly more overall complications in LVCs than in HVCs. Mehta et al (31) added that surgeon volume is also an independent risk factor for 30-day complication rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients transferred to the ICU also require special monitoring and intense care. Simultaneously, the number of complications greatly increased the in-hospital cost and length of hospitalization [ 6 ]. In a study of emergency department evaluation of suspected ICU patients, it was found that prolonged hospital stay in the emergency department increases the risk of death [ 7 ].…”
Section: Introductionmentioning
confidence: 99%